ROTAVIRUS INFECTION IN CHILDREN - A.V. Gorelov; D.V. Usenko ("Paediatrician" Publishers LLC, 2008)
Rotavirus - one of the most frequent reasons of acute gastroenteritis in children, especially in younger age. The modern conception of epidemiology, pathogenesis and treatment of rotavirus infection in children are presented in this literature review. Basic methods of treatment of rotaviral infection in present time are application of enterosorbents (smectite in doubled age specific dose) and oral regidratation, which can reduce duration of disease, decrease the risk of complications and intrahospital infections. Key words: children, rotavirus infection, treatment, smectite.